The effect of height in performing the underhand and overhand serve in volleyball for accurary and placement - Stromila, Ruth A. (My University, 1967)
The purpose of this study was to determine whether height was an advantage in executing the underhand and overhand serve in volleyball for accuracy and placement.
Keywords: Volleyball, Serve.